Voltage Oriented Control and Direct Power Control Strategies in solving under and overvoltage conditions for heavy load application on Malaysian Distribution Representative Network - Lee J.Y.; Verayiah R.; Ong K.H.; Ramasamy A.; Marsadek M.B. (Springer Science and Business Media Deutschland GmbH, 2023)
Benchmarking; Electric load flow; Pulse width modulation; Voltage distribution measurement; Control schemes; Direct power control; Load flow analysis; LV distribution networks; Reference voltages; Total harmonics distortions; Voltage dynamics; Voltage oriented control; Power control